Pemberdayaan Kader Remaja dan Remaja untuk Cegah Stunting dengan Gizi 1000 Hari Pertama Kehidupan di Desa Suka Maju Kec. Mestong Kab. Muaro Jambi Tahun 2023 - Wuryandari, Ajeng Galuh; Nurmisih, Nurmisih; Kusmaryanti, Pauline; Simanjuntak, Ry Eny Mian Marisa; Julaecha, Julaecha (Jurnal Abdimas Kesehatan (JAK), 2024)
Stunting instances persist in Suka Maju village, and there is a lack of a health disclosure program emphasizing the significance of 1000 HPK nutrition to avoid stunting. Additionally, there is a lack of projects to empower skilled young cadres. Teenagers have a crucial role in preventing stunting by being potential parents and catalysts for change, possessing extensive information about nutrition, and adopting healthy eating habits in their teenage years. This project aims to augment the involvement of young leaders and young individuals in understanding the significance of the initial 1000 days of life, with the aim of mitigating stunting in the hamlet of Suka Maju Kec. Mestong Kab. Muaro Jambi by the year 2023. The activity commenced with a survey of the location and an assessment of the needs of the partner areas, specifically the two villages and the surrounding regions. This was followed by the training of a group of six teenagers and 20 young adults. During the training, participants learned about the importance of using anthropometric methods to measure nutritional status, how to categorize nutritional status, how to properly use anthropometric tools, better health promotion strategies for teens about balanced nutrition, how to keep teens from having nutritional problems, and the role of teen leaders in stopping stunting. The training utilized effective instructional methods and empowered the cadres to plan and execute health promotion initiatives focused on preventing stunting and improving nutrition